2017
DOI: 10.1007/s00213-017-4566-0
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent cocaine exposure enhances goal-tracking behavior and impairs hippocampal cell genesis selectively in adult bred low-responder rats

Abstract: Rationale Environmental challenges during adolescence, such as drug exposure, can cause enduring behavioral and molecular changes that contribute to life-long maladaptive behaviors, including addiction. Selectively bred high-responder (bHR) and low-responder (bLR) rats represent a unique model for assessing the long-term impact of adolescent environmental manipulations, as they inherently differ on a number of addiction-related traits. bHR rats are considered “addiction-prone”, whereas bLR rats are “addiction-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…However, most of the previous studies evaluated drug and/or pro-depressive phenotype effects on cell genesis already in adult rats and did not explore the long-term consequences following an adolescent cocaine experience. In this line of thought, two of our prior studies (García-Cabrerizo et al, 2015; García-Fuster et al, 2017b) evaluated the effects of administering cocaine on hippocampal cell genesis at the same age-window of adolescent vulnerability (PNDs 33–39) used in the present study. Although one study showed deficits in the number of adult-born precursor cells (Ki-67+) and the number of surviving mature cells (49–51 days old BrdU+), these effects were seen only for bred low-responder rats (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the previous studies evaluated drug and/or pro-depressive phenotype effects on cell genesis already in adult rats and did not explore the long-term consequences following an adolescent cocaine experience. In this line of thought, two of our prior studies (García-Cabrerizo et al, 2015; García-Fuster et al, 2017b) evaluated the effects of administering cocaine on hippocampal cell genesis at the same age-window of adolescent vulnerability (PNDs 33–39) used in the present study. Although one study showed deficits in the number of adult-born precursor cells (Ki-67+) and the number of surviving mature cells (49–51 days old BrdU+), these effects were seen only for bred low-responder rats (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although one study showed deficits in the number of adult-born precursor cells (Ki-67+) and the number of surviving mature cells (49–51 days old BrdU+), these effects were seen only for bred low-responder rats (i.e. rats bred for low novelty-induced locomotor activity), as compared with bred high-responders (high novelty-induced locomotion), and were suggested to be attributed to an altered neuroplastic response to learning (García-Fuster et al, 2017b). On the other hand, the other study, which used the same outbred rats as in the present study, showed no changes on neurogenic markers (Ki-67+ proliferating cells and 38 days old BrdU+ surviving cells) following adolescent cocaine exposure (García-Cabrerizo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gi DREADD was injected bilaterally into the PrL (relative to bregma: Locomotor test. After 5 days of recovery from surgery, rats underwent a 60-min locomotor test in a novel environment as previously described [51]. Cumulative locomotor movements (vertical and horizontal movements) were calculated and a median split was used to classify rats as either high (HR) or low (LR) responders.…”
Section: Introductionmentioning
confidence: 99%
“…Lower gray matter volume in the prefrontal cortex, amygdala, and striatum have been observed in heavy chronic marijuana users (Battistella et al, ). Preclinical studies suggest adolescent cocaine exposure impairs hippocampal cell genesis (proliferation and survival) (Garcia‐Fuster, Parsegian, Watson, Akil, & Flagel, ), and adult hippocampal neurogenesis plays a role in cocaine addiction (Castilla‐Ortega et al, ). Further, substantia nigra hyperechogenicity was observed in young adults with a history of illicit stimulant use (cocaine, methamphetamine) who were currently abstinent and, such morphological changes in the substantia nigra, which may alter dopamine levels, are associated with developing Parkinson's disease later in life (Todd et al, ).…”
Section: Structural Brain Effects From Substance Use During Adolescencementioning
confidence: 99%